Pedagogy 21 Century from Perspective Information and Communication Technology (ICT): The Application in Learning - Razali, Hazrul Affendi Mohmad (Universitas Sebelas Maret, 2019)
The use of Information and Communication Technology (ICT) has provided great benefits in many fields including education. Lifestyle changes and the need to make the teaching and learning process more interesting and effective have driven the application of ICT in teaching. This paper aims to explain the influence of teacher knowledge and the process of implementing ICT in teaching. This process of implementing ICT requires teachers to be constantly aware and competitive with the changes that occur in teaching and learning. The impact of this paper is the change in teachers 'attitudes towards the need for ICT applications in teaching and teachers' thinking to cope with ever-changing technology.